Antibacterial activities of piper sarmentosum (kaduk) methanolic extract - Ibrahim, Maizatul Akma; Mohd Nazir, Syaza Sailah (UPM, 2019)
Piper sarmentosum or locally known as Kaduk is a tropical herbal plant that is well established for many traditional medicinal purposes. The antibacterial properties of methanolic extract for P. sarmentosum leaves have been investigated in this study. From the disc diffusion test, the methanolic extract of P. sarmentosum was found to be active against Gram-positive bacteria namely Staphylococcus saprophyticus (ATCC 15305) and Staphylococcus aureus (ATCC 25923) with zone of inhibition at 17.1 and 11.3 mm, respectively. Meanwhile, the extract showed no or minimal activity against Gram-negative bacteria (Klebsiella pneumoniae ATCC 700603, Pseudomonas aeroginosa ATCC 27853, Enterococcus aerogenes ATCC 13048, Shigella flexneri IMR S 430/07 B, Salmonella typhimurium IMR S 974/05 B) as well as Gram-positive bacteria of Bacillus subtilis (IMR B145/11C). Accordingly, further study by Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were conducted on S. saprophyticus and S. Aureus. The MIC value of methanolic extract for the tested S. saprophyticus and S. aureus were both at 7.5 mg/mL. The MBC showed bacteriostatic for S. saprophyticus and S. aureus at 15 mg/mL. The result of this study indicated that this Piper plant extract can be potential antibacterial agent in the future if the active component can be identified.